2023
DOI: 10.3390/mi14101923
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Acoustically Levitated Drops in Mid-Water

Jan-Paul Ruiken,
Jörn Villwock,
Matthias Kraume

Abstract: A low-impact acoustic levitation system has been developed to study immobilised single drops in liquid–liquid systems. The ability to observe liquid drops several millimetres in diameter for days enables fundamental research into a wide range of mechanisms. Non-invasive optical measurements with excellent optical accessibility are possible. This experimental work provides the basis for mass transfer studies, emphasizing the precise volume determination, signal noise, reproducibility, and the impact of the acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The authors recently demonstrated that the standing wave affects the spread of a substance dissolved inhomogeneously in the continuous phase. Two contrary effects were identified [ 12 ]: For one group of substances, the spread was not affected by the nodal plane above the drop. However, regions of maximum acoustic particle velocity at the outer tip of the horn of the Langevin transducer could not be overcome; For the other group of substances, the nodal planes act as barriers.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors recently demonstrated that the standing wave affects the spread of a substance dissolved inhomogeneously in the continuous phase. Two contrary effects were identified [ 12 ]: For one group of substances, the spread was not affected by the nodal plane above the drop. However, regions of maximum acoustic particle velocity at the outer tip of the horn of the Langevin transducer could not be overcome; For the other group of substances, the nodal planes act as barriers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The setup for low-impact acoustic levitation was used to measure immobilised dissolving single drops. The acoustic levitation measurements (ALMs) were conducted following the procedure obtained in [ 12 ]. Alternations to the settings would modify the acoustic environment, potentially leading to different results.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations